Detection of a latent soluble form of membrane type 1 matrix metalloprotease bound with tissue inhibitor of matrix metalloproteinases‐2 in periprosthetic tissues and fluids from loose arthroplasty endoprostheses. (25th October 2013) - Niarakis, Anna; Giannopoulou, Eleftheria; Ravazoula, Panagiota; Panagiotopoulos, Elias; Zarkadis, Ioannis K.; Aletras, Alexios J.
<x xml:space="preserve">Abstract</x> Membrane type 1 matrix metalloproteinase (MT1‐MMP) is implicated in pericellular proteolysis, and, together with tissue inhibitor of matrix metalloproteinases‐2 (TIMP‐2), in the activation of pro‐matrix metalloproteinase‐2 on the cell surface. It is expressed on the cell surface either activated or as a proenzyme. A soluble form of MT1‐MMP (sMT1‐MMP) has been previously identified in periprosthetic tissues and fluid of patients with loose arthroplasty endoprostheses. The aim of this study was to examine periprosthetic tissues and fluids from patients with loose arthroplasty endoprostheses, as well as tissues and fluids from patients with other disorders, for the presence of sMT1‐MMP, and to investigate its activation state and possible role. With antibody against MT1‐MMP, a protein with molecular mass of ~ 57 kDa was detected by western blotting in all samples tested, representing a soluble form of MT1‐MMP, which cannot be ascribed to alternative splicing, as northern blotting showed only one transcript. With various biochemical methods, it was shown that this species occurs in a latent form bearing the N‐terminal prodomain, and, additionally, it is bound to TIMP‐2, which appeared to be bound via its C‐terminal domain to a site different from the active site. Cell ELISA and immunohistochemical analysis revealed that, besides fibroblasts, all other cells, such as inflammatory, epithelial, endothelial, giant and cancer cells, express MT1‐MMP on their plasma membrane as a proenzyme. Taking into account the proteolytic abilities of MT1‐MMP, the latent sMT1‐MMP–TIMP‐2 complex could be considered as a new interstitial collagenase. However, the exact role, the production mechanism and the cell origin of this complex remain to be elucidated.